Global glaciological models: a new stage in the development of methods for predicting glacier evolution. Part 2. Formulation of experiments and practical applications - T. Postnikova N.; O. Rybak O.; Т. Постникова Н.; О. Рыбак О. (Diversity, 2022)
Global glacier models provide a new way for studying glaciers on the regional and global scales. They make it possible to perform predictive experiments - for example, to forecast changes in glaciation and river runoff, and diagnostic ones – to identify regularities in the behavior of glaciers (a response time to climate change) taking account of their characteristics. The characteristics and design of global glacier models were described in the first part of the review (see Postnikova T.N., Rybak O.O. Global glaciological models: a new stage in the development of methods for predicting glacier evolution. Part 1. General approach and model architecture. Led i Sneg. Ice and Snow. 2021, 61 (4): 620–636. [In Russian]. doi:10.31857/S2076673421040111.). In the second part, we present the methods for setting up of numerical experiments with these models, including model initialization, climate forcing, calibration, and validation procedures. The only way to provide the climate forcing of a glaciological model on a regional or global scale is to use low-resolution reanalysis or output of climate modeling on GCMs or RCMs that needs to use a process of scaling to reproduce the local climate in a complex topography where glaciers are usually located. Calibration of mass balance complements the downscaling of climate forcing for each glacier, and usually it includes parameters responsible for the glacier's response to climate change. Sampling from the Latin hypercube and Bayesian inversion are some of the methods discussed in this connection. In this review we present a comparative description of the selected global glaciological models, the results obtained by both diagnostic and prognostic ones, as well as scale and significance of them. We discuss also ways for further development of global glacier models, in particular the inclusion of 3D-modeling and the moraine (debris cover) block. The difficulties arising in a process of modeling glaciation of a particular mountain region or several regions are noted. Глобальные ...